Pourfour du Petit Syndrome Associated With Right Eye Pressure. Issue 6 (13th March 2017) - Evans, Randolph W.; Garibay, Adam; Foroozan, Rod
Abstract : Pourfour du Petit (PDP) syndrome is a rare disorder characterized by ipsilateral mydriasis, eyelid retraction, and hemifacial hyperhidrosis caused by hyperactivity of the ipsilateral oculosympathetic pathway. A case is presented of PDP syndrome associated with likely ipsilateral occipital neuralgia. We review the causes and co‐morbidities and the clinical features of PDP.